Families of linear generating functions for polynomials in two variables - Özarslan, Mehmet Ali; Altın, Abdullah; Erkuş, Esra (Taylor & Francis, 2006)
In the present paper, we derive various families of linear, mixed multilateral and multilinear generating functions for a class of polynomials in two variables. Some further results of the above types are also discussed.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Hermite-Kampé de Fériet polynomials, Generating functions, Lagrange-Hermite polynomials; Jacobi polynomials, Lagrange polynomials, Pochhammer symbol, MATHEMATICS; APPLIED, MATHEMATICS, HYPERGEOMETRIC POLYNOMIALS; generating functions, Hermite-Kampe de Feriet polynomials